International Financial Reporting Standards : A Practical Guide, Newly Revised Edition - Van Greuning, Hennie (Washington, DC: World Bank, 2012)
In response to the global financial crisis in 1998, an initiative was launched to strengthen the global financial structure, and, although the International Accounting Standards (IAS) have been in existence for some time, it is believed such initiative will help promote transparency in financial reporting, and acceptance of its wide range of international best practices. This publication provides guidance, and summarizes each IAS, while each chapter contains a simple case study, emphasizing the practical application of key concepts in a particular standard. On how to use this publication, the authors created a template to facilitate discussion of each standard: 1) "problems addressed" identifies the main objectives, and key issues of the standard; 2) "scope of the standard" identifies specific transactions covered by a standard; 3) "accounting treatment" lists the specific accounting principles, bases, conventions, rules, and practices to be adopted for compliance with a particular standard; and, 4)"disclosure" describes the manner in which the financial, and non-financial items should be presented in financial statements, including aspects that should be disclosed in such financial statements.